Effectiveness of case scenario‐based teaching to transition international Master of Public Health students specialising in health promotion from memorization to critical thinking. (28th June 2022) - Hosseinzadeh, Hassan; Ratan, Zubair Ahmed; Shnaigat, Mahmmoud; Edwards, Joseph; Verma, Iksheta; Niknami, Marzieh; Dadich, Ann
Abstract: Issue addressed: Critical thinking is essential to health promotion to overcome increasingly complex health issues. International students from Middle East and Asia are however disadvantaged when required to demonstrate critical thinking mainly because of their previous training in memorisation. This study addresses this need by evaluating the effect of case scenario‐based teaching on transition from memorisation to critical thinking among international students in an Australia university. Methods: This was a pre and post intervention study and data were collected from a convenience sample of 79 international Master of Public Health students specialising in health promotion in 2019 at the University of Wollongong. Results: Most of the participants were female (73.4%) and aged 25 years or older (64.6%), predominantly from India (40.5%), Nepal (31.6%) and Saudi Arabia (11.4%). A paired t ‐test analysis showed that the intervention – case scenario‐based teaching – significantly improved the mean post‐intervention critical thinking skills ( P  < 0.001). Case studies improved critical thinking among international students, irrespective of demographic attributes. Multiple regression analyses indicated that critical thinking predicted 78.6 of the total marks, after controlling for demographic attributes. In terms of assessment marks, improved multiple solutions skills yielded better marks for tutorial participations; while improved problem identification skills improved marks for report assessments and exams. Improved communication skills led to better marks for essay assessments. Conclusions: Case studies improved critical thinking and was a reliable predictor of student performance among the participants. So what?: This study makes a strong case for case scenario‐based teaching to improve critical thinking among international students. However, given the limitations of this study, including the small, non‐representative sample, further testing is required.